Contributions of the 8-Methoxy Group of Gatifloxacin to Resistance Selectivity, Target Preference, and Antibacterial Activity against Streptococcus pneumoniae - Fukuda, Hideyuki (American Society for Microbiology, 2001)
Gatifloxacin (8-methoxy, 7-piperazinyl-3′-methyl) at the MIC selected mutant strains that possessed gyrA mutations at a low frequency (3.7 × 10(−9)) from wild-type strain Streptococcus pneumoniae IID553. AM-1147 (8-methoxy, 7-piperazinyl-3′-H) at the MIC or higher concentrations selected no mutant strains. On the other hand, the respective 8-H counterparts of these two compounds, AM-1121 (8-H, 7-piperazinyl-3′-methyl) and ciprofloxacin (8-H, 7-piperazinyl-3′-H), at one and two times the MIC selected mutant strains that possessed parC mutations at a high frequency (>2.4 × 10(−6)). The MIC of AM-1147 increased for the gyrA mutant strains but not for the parC mutant strains compared with that for the wild-type strain. These results suggest that fluoroquinolones that harbor 8-methoxy groups select mutant strains less frequently and prefer DNA gyrase, as distinct from their 8-H counterparts. The in vitro activities of gatifloxacin and AM-1147 are twofold higher against the wild-type strain, eight- and twofold higher against the first-step parC and gyrA mutant strains, respectively, and two- to eightfold higher against the second-step gyrA and parC double mutant strains than those of their 8-H counterparts. These results indicate that the 8-methoxy group contributes to enhancement of antibacterial activity against target-altered mutant strains as well as the wild-type strain. It is hypothesized that the 8-methoxy group of gatifloxacin increases the level of target inhibition, especially against DNA gyrase, so that it is nearly the same as that for topoisomerase IV inhibition in the bacterial cell, leading to potent antibacterial activity and a low level of resistance selectivity.